DEVELOPMENT OF SPIRITUAL INTELLIGENCE BASED COLLABORATIVE LEARNING - Komalasari, Oom; Rohmah, Asyifa Nur; Marwiyah, Wiwi; Aidah, Nurul (EDUCATIONE, 2023)
Developing spiritual intelligence can be interpreted as all efforts, steps, activities carried out both independently and with the help of others in order to develop spiritual intelligence. The development of this spiritual aspect does not have to be a program or a subject that specifically provides material on spirituality. However, this spiritual aspect can be developed more broadly and integrated through any activities. Although Zohar and Marshal only stated that we need a 'religious framework' as a guide to have and increase SQ potential, in this study, this will be used as something that is mandatory to then frames the development of spiritual intelligence. Thus the development of spiritual intelligence is an effort to develop, encourage and invite humans to be more advanced in matters relating to psychological, spiritual, mental, moral, or those relating to the spirit or soul, as well as working with their efforts or assumptions regarding transcendental values (divine values) with a monotheistic (integralistic) mindset and only because of Allah SWT.